Communicating Seismic Risk Information: The Effect of Risk Comparisons on Risk Perception Sensitivity - Savadori, Lucia; Ronzani, Piero; Sillari, Giacomo; Di Bucci, Daniela; Dolce, Mauro (Frontiers in Communication, 2022)
Communicating seismic risk to individuals can be difficult for an institution because it involves providing technical and scientific information, including the low probability of an adverse event, that is not always easy to understand. One way to facilitate understanding of low probabilities is to provide comparisons with the probability of occurrence of other more familiar events. In a randomized trials experiment, we investigated the effect of providing individuals with a set of risk comparisons on their sensitivity to different levels of seismic risk (1 in 100, 1 in 1,000, and 1 in 10,000). The findings show that providing risk comparisons increased individual risk sensitivity to information about the likelihood of experiencing a seismic event. Our findings are explained by the evaluability hypothesis, which states that a single probability value is better understood if the recipient is given some reference data to evaluate it. Our results have implications for disaster risk communication, providing ways to increase risk awareness and, consequently, disaster prevention.